Experiencing culture of everyday life by international exchange students. Perspective of arts-based research - Pryszmont, Martyna; Achremowicz, Hanna; Pilawska-Gronostaj, Roksana; Wylęgły, Kamila; Chmiel, Anna (Edukacja Dorosłych, 2022)
The text is an attempt to introduce and initiate a research project which focuses on experiencing the culture of daily living by international exchange students. The authors present major theoretical reflections on the issues of experience and culture of everyday life; they also characterize the community of student– participants of international exchange programs. (Re)cognition and understanding of experience is a methodological challenge, especially in regard to dialogue-oriented intercultural education. The authors decided to explore the issue, using arts-based research. In this model, the role of researchers-facilitators is to introduce the respondents into the research process by inviting them to participate in joint activities focusing on cognitive, artistic, social, and educational objectives. Such participation and cooperation are supposed to result in generating critical knowledge necessary to improve the respondents’ daily life. In the last part of the text, the authors conduct an initial analysis of the selected international exchange programs. The goal of the characteristics of ERASMUS, ISEP, AIESEC, CEEPUS programs is to outline the official objectives and priorities assigned to formal education. In this perspective, when planning their original research, the authors asked the following question: How are these priorities present, as complementary to non-formal education, in experiencing the culture of everyday life by exchange students?